Mengembangkan Strategi Pemasaran Omnichannel Menggunakan Customer Journey Mapping pada Perusahaan Ritel Olahraga: Studi Kasus Decathlon Indonesia - Qolbi Alfarizi Rahman; Ira Fachira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze customer interaction patterns within a cross-channel retail system, identify experiential gaps along the purchasing journey, and formulate a more integrated marketing strategy using a structured customer journey mapping approach. The research addresses the increasing fluidity of customer behavior across digital and physical channels, particularly in the context of omnichannel retail implementation at Decathlon. A quantitative descriptive method was employed, using a Likert-scale survey distributed to customers who had utilized more than one channel during their purchase journey. The instrument was developed based on consumer decision-making theory and structured journey analysis concepts. Data were analyzed through descriptive statistical techniques to identify response distribution, levels of agreement, and indicators of experiential inconsistency. The findings indicate that customers actively engage in multi-channel interactions during the pre-purchase stage, mainly through digital information search followed by in-store verification. While purchase decisions are influenced by convenience and trust, some respondents experience friction during channel transitions. Post-purchase satisfaction and repurchase intention are relatively high; however, complaint handling remains an area for improvement. The study concludes that although structural channel integration exists, experiential continuity has not yet been fully optimized.